Identifying benefit flows: studies on the potential monetary and non-monetary benefits arising from the international treaty on plant genetic for food and agriculture - Stannard, C.; Moeller, N. I. (Food and Agriculture Organization of the United Nations, 2013)
This volume is published in connection with the research project, Identifying the Potential Monetary and Non-monetary Benefits Arising from the Utilization of Plant Genetic Resources under the Multilateral System of the International Treaty on Plant Genetic Resources for Food and Agriculture, carried out with the financial support of the Government of Australia. The project prepared five interlinked studies between July 2011 and March 2012, and their reports are published in this book. Study 1 – Adam Drucker and Francesco Caracciolo (2012) The Economic Value of Plant Genetic Resources for Food and Agriculture. Study 2 – Clive Stannard, Francesco Caracciolo & Peter Hillery (2012) Modelling Payments to the Benefit-Sharing Fund, Resulting from the Standard Material Transfer Agreement. Study 3 – C. S. Srinivasan (2012) Assessing the Potential for Monetary Payments from the Exchange of Plant Genetic Resources Under the Multilateral System of the International Treaty on Plant Genetic Resources for Food and Agriculture. Study 4 – Paul Oldham & Stephen Hall (2012) Intellectual Property, Informatics and Plant Genetic Resources. Study 5 – Maryline Guiramand, Nina Isabella Moeller & Mario Marino (2012) Plant breeding and the use of the Standard Material Transfer Agreement: Consultation with Plant Breeding Experts.